Perencanaan SPAM Mata Air Dedari Untuk Pemenuhan Kebutuhan Air Masyarakat Desa Sibetan - Kadek Windy Candrayana; AA Sagung Dewi Rahadiani; Ni Wayan Nurwarsih (Universitas Warmadewa, 2025)
This community service activity was carried out to support Sibetan Village, particularly Banjar Telaga, which is still facing limited access to clean water. The potential to meet clean water demand comes from the Dedari Spring, with a discharge of 1.5 liters/second, which is considered sufficient to serve 50 households at present and for the next 15 years. However, the spring is located below a cliff with an elevation difference of 107.78 meters from the reservoir point, thus requiring pumping technology for distribution. The methods used included field surveys, discharge measurements, water demand analysis, and the technical design of a Drinking Water Supply System (SPAM). The design process was carried out using hydraulic simulations with WaterCAD software to determine pump capacity, reservoir dimensions, and pipeline networks. Student involvement in mapping and analysis also provided academic value and practical experience in applying their knowledge. The results of the activity include a SPAM design equipped with a pump of 120-meter head, a discharge of 1 liter/second, a reservoir capacity of 30 m³, and a pipeline network of 1,686 meters. The network pressure meets the required standards, and the design is complemented with detailed drawings and a cost estimate of IDR 447,628,512.62. This design is expected to improve clean water access, support funding proposals, and align with the SDGs target of providing clean water and proper sanitation.